The Efect of Problem Posing Learning Assisted Origami Paper on Creative Thinking Skill Students - yono, Mulyono Yono; Djazuli, Akhmad (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
Abstract. The research aimed to see the effect problem posing to creative thinking skills and students achievement-assisted origami paper. Problem posing used to increase students skill not only to find knowledge accidentally but trough the effort to find relationship knowledge their learn. The result from relationship knowledge was question or answer from their filed self so they understand the way to solve the problem using origami paper to attract student’s attention and strengthen student understanding. Literacy study was used in this research. The data obtained were compiled, analyzed, and concluded to get conclusions about the effect of origami paper in the problem posing learning to creative thinking skill students. Based on the results of this research using literacy studies from several research journals and articles show that problem posing has effect of origami paper on creative thinking skills students and students achievement.